The Effect of GDP Growth and Inflation on Changes in Stock Company Prices Listing on the IDX 2016-2018 - Dianita, Mirna; Hadian, Niki; Ali, Muhammad; Lisa Aryanti, Maya (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted to determine the effect of Gross Domestic Product (GDP) growth and inflation on changes in the stock price of infrastructure companies listed on the Indonesia Stock Exchange in the period of 2016–2018. The data sources used in this study are secondary data of three infrastructure companies, namely PT. Citra Marga Nusaphala Persada, Tbk (CMNP), PT. Jasa Marga (Persero), Tbk (JSMR), and PT. Nusantara Infrastructure, Tbk (META). The data are obtained from the Indonesia Stock Exchange, Bank Indonesia, and the Central Bureau of Statistics. The analysis technique used in this study is multiple regression analysis. The results show that both partially and simultaneously, the GDP and inflation variables had significant effects on changes in the stock price of infrastructure companies.